Positive deviance for dual-method promotion among women in Uganda: study protocol for a cluster randomized controlled trial - Kosugi, Hodaka; Shibanuma, Akira; Kiriya, Junko; Ong, Ken Ing Cherng; Mucunguzi, Stephen; Muzoora, Conrad; Jimba, Masamine (Trials, 2020)
Background: Dual-method use is known as the most reliable protection against unintended pregnancies and sexually transmitted infections, including HIV. However, it is not commonly used in sub-Sharan Africa, especially among women using highly effective contraceptives. This article describes a protocol to evaluate the effect of an intervention formulated under the positive deviance approach for promoting dual-method use in Uganda. Methods: A total of 150 women will be interviewed using a structured questionnaire to find those practicing dual method use. In-depth interviews will then be conducted with all women using the dual method and 10 women using only highly effective contraceptives to identify their unique practice. Then, a cluster randomized controlled trial will be conducted to examine the effect of an intervention formulated under the positive deviance approach on dual-method uptake and adherence. Twenty health facilities will be randomized to an intervention or control arm and 480 women will be enrolled in each group. The participants will be followed up for 8 months. Discussion: This trial focuses on women who already adapted dual-method use and identifies their unique solutions to promote dual-method use. This trial could tackle barriers for dual-method use, which expert outsiders may fail to recognize, by analyzing and promulgating their unique behaviors. This study could provide evidence that the positive deviance approach can address unintended pregnancies and sexually transmitted infections as well as other health problems which usual approaches have failed to address
Keywords: Positive deviance; Dual-method use; Contraception; Unintended pregnancy; Sexually transmitted infection; HIV/AIDS